Challenges and Prospects of Islamic Banking in Nigeria - Jibril Mika’il, Usman; Abdul-Lateef Aremu , Tijani; Lawal Sikiru, Alimi (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The veracity of the universality of Islamic faith is, among other things, the fact that it does not only regulate human activities, but also proffer the best solutions to the myriad of human problems. Nigeria, no doubt, is not having the best from the banking industry in her bid to secure economic emancipation in the comity of nations, hence, the need for alternative banking system. This paper, therefore, examines the concept of Islamic banking as a financial system as well as its challenges and prospects in the Nigerian economy. The paper posits that Islamic banking system will bring transformation to all sectors of the Nigerian economy vis-a-viz, eradication of poverty, equitable distribution of income and employment opportunities in the country through effective mobilization and allocation of resources. Recourse shall be made to relevant materials and reports in order to justify the prospects of Islamic banking in Nigeria. The paper concludes that effective laws need to be promulgated in order to foster the establishment and operation of more Islamic banks in the country. Also, orientation of the people towards a better understanding of the Islamic banking system will go a long way in making the country benefit maximally from the system.